Incidence trends of prostate cancer in Sarawak, Malaysia: a 20-year population-based analysis - Emmanuel Joseph Fong; Kung Yee Wong; Chuo Yew Ting; Diana Jawa; Abdullah Hamdan; Mastulu Wahab; Azizah Azhar; Eunice Melissa Joseph; Johnny Pangkas; Choo Huck Ooi (Discover Public Health)
Abstract This study explored the incidence trends of prostate cancer within the Borneo State of Sarawak, with its unique population demography, over a 20-year period. Data was collected from cancer registries spanning from 1996 to 2015, focusing on annual incidence rates and demographics. Joinpoint regression analysis revealed an increasing trend over the years with significant Annual Percent Change (APC) of 3.86 (95% CI 1.3, 7.2). The mean age at diagnosis was significantly trending downwards with an Average APC of − 0.31 (95% CI − 0.5, − 0.1) over the times. Despite having a lower incidence rate compared to Oceania and North America, the rise in prostate cancer incidence within the Asia-Pacific region has been recognised as an area of public health concern and requires further research. Continued efforts in early detection and treatment advancements are substantial.